Mechanism of paracetamol-induced hypotension in critically ill patients: a prospective observational cross-over study - Krajčová, Adéla; Matoušek, Vojtěch; Duška, František (Australian critical care, 2013)
OBJECTIVE: To elucidate the mechanism of hypotension following intravenous administration of paracetamol (acetaminophen) to patients on the Intensive Care Unit. DESIGN: Prospective observational cross-over study. SETTING: Intensive Care Unit, University Hospital Královské Vinohrady, Prague, Czech Republic. METHODS: Ventilated critically ill patients monitored by PiCCO and administered intravenous paracetamol at the same time were eligible for the study. We recorded haemodynamic indices, as well as core and peripheral temperatures, continuously for 3 h after the dose of paracetamol. Ranitidine was then used as a control drug known not to influence haemodynamics. RESULTS: We included 6 subjects, and recorded 48 cycles of observations after administration of paracetamol, and 35 cycles after administration of the control drug. Haemodynamic parameters were not different at the baseline and administration of control drug did not result in any change in haemodynamics. After intravenous paracetamol, mean arterial pressure (MAP) dropped by 7% (p<0.001) with a nadir at the 19th minute. In 22 measurement cycles (45%) we noted >15% reduction in MAP with paracetamol. Analysis of these cycles suggests that hypotension with paracetamol can be caused by reduction of both cardiac index and systemic vascular resistance. In febrile cycles paracetamol caused narrowing of the gradient between central and peripheral temperatures suggesting skin vasodilation. These changes were not correlated to a change of systemic vascular resistance at any time point. CONCLUSION: Hypotension with intravenous paracetamol in critically ill patients is caused by a reduction of both cardiac output and systemic vascular resistance. We did not demonstrate any relation between haemodynamic changes and antipyretic action of paracetamol. A possibility that cardiac output is reduced with paracetamol might be clinically important.
Keywords: Female; klinické křížové studie; tělesná teplota; intravenózní infuze; kritický stav; ženské pohlaví; Hemodynamics; hemodynamika; Paracetamol; lidé; Cross-Over Studies; prospektivní studie; paracetamol; Male; Body Temperature; Aged; Hypotension; Prospective Studies; Infusions, Intravenous; antipyretika; Antipyretics; Acetaminophen; hypotenze; lidé středního věku; senioři; mužské pohlaví; Haemodynamics; Cardiac output; Middle Aged; Critical Illness; Humans